Mobilizing agrobiodiversity in India to support planet-friendly school meal programs: Insights from Participatory Crop Selection for School Meal Diversification - Shijagurumayum, Meghajit Sharma; Estrada Carmona, Natalia; Jones, Sarah; Elias, Marlene; Zaremba, Haley Carter (2025)
This study examines how India’s school meal programs can better use local agrobiodiversity to address persistent gaps in nutrition, sustainability, and meal acceptability. It links school-level meal practices with local farm and landscape contexts to analyze how food, production, and procurement systems interact under state-defined but locally implemented menu frameworks. Within this broader analysis, the study documents a participatory crop identification and validation process conducted in Mandla district. Community actors assessed locally available species across agroecological performance, nutrition, farmer experience, and procurement feasibility.